2023
DOI: 10.3389/fnhum.2023.1202103
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate prediction of long COVID headache in adolescents using gray matter structural MRI features

Abstract: ObjectiveHeadache is among the most frequent symptoms after coronavirus disease 2019 (COVID-19), so-called long COVID syndrome. Although distinct brain changes have been reported in patients with long COVID, such reported brain changes have not been used for predictions and interpretations in a multivariate manner. In this study, we applied machine learning to assess whether individual adolescents with long COVID can be accurately distinguished from those with primary headaches.MethodsTwenty-three adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A 2022 study comparing pediatric NDPH patients to healthy controls found decreased cortical thickness and altered resting-state functional connectivity in areas involved in cognitive inhibitory control and pain-related processes [ 10 ]. Interestingly, a 2023 study used structural MRI to distinguish between adolescents with long COVID headache and those with primary headache disorders, including NDPH, revealing potential biomarkers for conditions that, so far, have only clinical criteria [ 32 ]. While a 2022 adult study did not show any gray matter differences in NDPH compared to healthy controls [ 33 ], a 2023 study investigating patients aged 14–70 showed changes in brain morphology such as cortical surface area, cortical thickness, and GM volume, accompanied by abnormal cortical neural activity [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2022 study comparing pediatric NDPH patients to healthy controls found decreased cortical thickness and altered resting-state functional connectivity in areas involved in cognitive inhibitory control and pain-related processes [ 10 ]. Interestingly, a 2023 study used structural MRI to distinguish between adolescents with long COVID headache and those with primary headache disorders, including NDPH, revealing potential biomarkers for conditions that, so far, have only clinical criteria [ 32 ]. While a 2022 adult study did not show any gray matter differences in NDPH compared to healthy controls [ 33 ], a 2023 study investigating patients aged 14–70 showed changes in brain morphology such as cortical surface area, cortical thickness, and GM volume, accompanied by abnormal cortical neural activity [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…While many of the other pediatric-focused studies looked at emerging treatment options, they were limited by sample size, as the studies involved relatively few patients and the numbers of NDPH patients within that sample was, with one exception [ 13 ], within the single to low-double digit range [ 9 , 11 , 45 , 46 ]. Likewise, while the studies showing potential biomarkers on MRI, functional connectivity, and brain mapping represent a fascinating and exciting new avenue in diagnosis, the sample sizes were still very low [ 32 , 34 , 35 ]. Further studies are needed to provide new targets for treatment and diagnosis, as well as outcome measures that may more accurately reflect meaningful changes in patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To predict schizophrenia using rsFC, we used connectome-based predictive modeling (CPM), a data-driven protocol for developing predictive models of brain–behavior relationships ( 12 ). We modified the CPM approach by replacing its core learning algorithm with a linear support vector machine (SVM) ( 28 , 29 ). We briefly explain how the CPM-SVM procedure works.…”
Section: Methodsmentioning
confidence: 99%